Understanding capital markets volume II : the financial environment and the flow of funds in the next decade - Sametz, Arnold W.; Wachtel, Paul. (Lexington, Mass. : Lexington Books, 1977)
This book is a compilation of essays from different authors on various aspect of issues that will shape the financial environment of the United States. It discusses the forecast methodologies used and point out some areas where differences of opinion exist.
Includes bibliographical references and index.
usc 01/08/2017
Loans
Keywords: Finance; Flow of funds; Saving and investment; Capital markets; United States